Complement-Dependent Cytotoxicity Assay for Differentiating West Nile Virus from Japanese Encephalitis Virus Infections in Horses - Kitai, Yoko (American Society for Microbiology (ASM), 2010)
A complement-dependent cytotoxicity (CDC) assay was established to measure antibodies to the West Nile virus (WNV) nonstructural protein 1 (NS1) in horses. Sera collected from a WNV-infected horse mediated lysis of WNV NS1-expressing cells in a dose-dependent manner at higher percentages than sera from a Japanese encephalitis virus (JEV)-infected horse. The percentages of specific lysis for sera diluted 1:10 to 1:80 were <19.8% (assay cutoff) for almost all of the 100 JEV-infected or uninfected horses tested, in contrast to 55 to 76% in WNV-infected horses. Experimental infection revealed that horses became anti-WNV NS1 antibody positive 10 days after WNV infection. This study demonstrated the utility of this assay for differentiating WNV from JEV infections in horses.